Urban Chinese midwives' knowledge, attitudes and practices toward umbilical cord blood donation. (February 2019) - Lee, K.P.; Lau, Eleven Y.; Sumerlin, Timothy S.; Kim, Jean H.
Highlights: Hong Kong midwives possess positive attitudes and good knowledge of cord blood. Yet giving cord blood-related information to expectant mothers is uncommon. Improving education, perceptions and clinic protocols will likely increase advising. Abstract: Objective: This study aimed to assess the knowledge, attitudes and factors associated with promotion of umbilical cord blood (CB) donation by Chinese midwives to expectant mothers. Design: An anonymous cross-sectional survey using self-administered questionnaires. Setting: Hong Kong, China. Participants: One-hundred-and-forty-seven registered Chinese midwives were recruited by convenience sampling from government obstetric clinics and public and private hospitals. Measurements and findings: In addition to collecting demographic background information, the study examined the midwives' cord blood-related knowledge and perceptions as well as past-year practices and future intention of giving cord blood advice. Hong Kong midwives generally showed high levels of knowledge about the medical uses of cord blood but they were not as familiar with the administrative, legal and financial aspects of donation and storage. Only about 10% had received formal cord blood training and the majority felt that it should be integrated into midwifery program curricula. Although the midwives showed strong positive attitudes towards cord blood donation, only 10.9% consistently gave information and 7.5% consistently advised cord blood donation to expectant mothers in the preceding year while slightly higher percentages planned to do so in the future. In the multivariable models, higher educational attainment and hospital employment were the most consistent predictors of past-year practices of giving cord blood information and future intention to provide advice. Higher score in cord blood-related attitudes was significantly associated with giving past-year cord-blood advice, future intention to provide advice and future intention to recommend donation in the multivariable models. Key barriers to advising expectant mothers were the lack of a formal work protocol, lack of time in the clinic routine and fear of criticism by peers. Key conclusions and implications for practice: Increasing education, improving perceptions and changing workplace protocols will likely increase cord blood advising by Hong Kong midwives to their patients.